Atomic-scale detection of individual lead clusters confined in Linde Type A zeolites. Issue 26 (10th June 2022) - Fatermans, Jarmo; Romolini, Giacomo; Altantzis, Thomas; Hofkens, Johan; Roeffaers, Maarten B. J.; Bals, Sara; Van Aert, Sandra
Abstract : By combining TEM with image simulations and XRD, a strategy is proposed for enabling local detection of confined Pb clusters in Linde Type A zeolites with Pb loadings as low as 5 wt%. Abstract : Structural analysis of metal clusters confined in nanoporous materials is typically performed by X-ray-driven techniques. Although X-ray analysis has proved its strength in the characterization of metal clusters, it provides averaged structural information. Therefore, we here present an alternative workflow for bringing the characterization of confined metal clusters towards the local scale. This workflow is based on the combination of aberration-corrected transmission electron microscopy (TEM), TEM image simulations, and powder X-ray diffraction (XRD) with advanced statistical techniques. In this manner, we were able to characterize the clustering of Pb atoms in Linde Type A (LTA) zeolites with Pb loadings as low as 5 wt%. Moreover, individual Pb clusters could be directly detected. The proposed methodology thus enables a local-scale characterization of confined metal clusters in zeolites. This is important for further elucidation of the connection between the structure and the physicochemical properties of such systems.